2011
DOI: 10.5897/ajb11.2624
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NaCl salinity on maize (Zea mays L.) at germination and early seedling stage

Abstract: The response of eight maize hybrids against five different salinity levels namely 0, 60, 120, 180 and 240 mM) were studied at germination and early seedling stage. This investigation was performed as factorial experiment under completely randomized design (CRD) with three replications for each salinity level. Analysis of variance (ANOVA) showed that there were significant differences (P < 0.05) between salinity stress levels, hybrids and interaction effects for all investigated traits. Supplementary analysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 18 publications
9
44
0
1
Order By: Relevance
“…Our results indicated that high salinity remarkably inhibited the germination of seed and delayed germination time in sunflower. Similar results were recorded in other crops such as rice (Oryza sativa) (Xu et al 2011), wheat (Triticum aestivum) (Akbarimoghaddam et al 2011), and maize (Zea mays) (Khodarahmpour et al 2012). The negative effects of high salinity may be due to ion toxicity on seed germination, as a consequence of a coincident increase in anion and cation (Panuccio et al 2014).…”
Section: Resultssupporting
confidence: 67%
“…Our results indicated that high salinity remarkably inhibited the germination of seed and delayed germination time in sunflower. Similar results were recorded in other crops such as rice (Oryza sativa) (Xu et al 2011), wheat (Triticum aestivum) (Akbarimoghaddam et al 2011), and maize (Zea mays) (Khodarahmpour et al 2012). The negative effects of high salinity may be due to ion toxicity on seed germination, as a consequence of a coincident increase in anion and cation (Panuccio et al 2014).…”
Section: Resultssupporting
confidence: 67%
“…Althought the MR219-4, MR219-9 and MR219 seeds germinated in the higher PEG levels, the MR220 (-1.2 MPa), MR159 and MR211 (-0.8 and -1.2 MPa) seeds could not germinate at all (Table 8). Reportedly, the reduction in germination by increasing the PEG level was possibly due to high seed nutrient imbalance, toxic ions, and reduced soluble osmotic potential (Khodarahmpour et al, 2014). In contrast to all the above parameters, average G% GVI G% GVI G% GVI G% G% GVI G% GVI GVI MR219 MR219-4 MR219-9 MR220 MR159 MR211 germination time was increased by increasing the PEG level in all varieties.…”
Section: Peg Primingmentioning
confidence: 76%
“…In contrast to all the above parameters, average G% GVI G% GVI G% GVI G% G% GVI G% GVI GVI MR219 MR219-4 MR219-9 MR220 MR159 MR211 germination time was increased by increasing the PEG level in all varieties. Increment in the mean germination with the increasing of osmotic potential by NaCl and PEG were documented in rice, maize and safflower previously (Farooq et al, 2006b;Khodarahmpour et al, 2014). The PEG content affected the proline accumulation in different rice varieties significantly.…”
Section: Peg Primingmentioning
confidence: 91%
“…While the longest roots were determined in HELEN (19.81 cm) and Pasha (19.13 cm) cultivars, the shortest roots were in PR31A34 (15.53 cm) maize cultivar. It has also been reported by Khodarahmpour et al (2012) that root lengths of different maize genotypes showed significant differences in different salinity levels.…”
Section: Root Lengthmentioning
confidence: 91%
“…For this reason, the length of roots ensures main clue to response of plants to salinity stress (Khodarahmpour et al, 2012).…”
Section: Root Lengthmentioning
confidence: 99%